Assessment of sleep in pediatric cancer patients - Dilek İnce; Bengü Demirağ; Tuba Hilkay Karapınar; Yeşim Oymak; Yılmaz Ay; Arife Kaygusuz; Ersin Töret; Canan Vergin (The Turkish Journal of Pediatrics)
The purpose of the study is to describe sleep habits, assess the prevalence of sleep disturbances in pediatric cancer patients and healthy controls, and to compare sleep patterns, sleep problems. One hundred-thirty-five patients and 190 healthy controls were evaluated. Healthy children matched for age, sex, economic status, parental education and family structure constituted the control group. Sleep was evaluated by using the Children`s Sleep Habits Questionnaire (CSHQ). Sleep problems were detected in half of patients. There were no significant differences in total sleep score and subscale scores between patients and controls. Solely the wake-time was found significantly different between patients and controls. Although our results indicated that neither childhood cancer survivors nor patients with cancer during treatment period had more sleep problems than their healthy peers, sleep problems were not uncommon in whole study group. This study underlines the need to screen, assess and manage sleep problems in children with diagnosis of cancer.